Development of single phase bimodal microstructure in bulk ultrafine-grained low carbon steel. (2020) - Singh, Raj Bahadur; Mukhopadhyay, N.K.; Sastry, G.V.S.; Manna, R.
Highlights: Ultra high strength bulk nanostructured LCS is produced by ECAP followed by cryorolling. Flash annealing can produce bimodal microstructures in single phase LCS. 600 °C is found to be optimum temperature for flash annealing. Novel microstructure of single phase bimodal grains distribution. Recovery, recrystallization and secondary recrystallization. Abstract: The low carbon steel (LCS) rods were plastically deformed at room temperature up to a very high strain level by equal channel angular pressing (ECAP). ECAPed samples were further cryo-rolled at subzero temperature up to 94% area reduction. After plastic deformation, samples were annealed for short period at 475–675 °C temperature range. Optical microscopy and transmission electron microscopy are used to characterize primary microstructure and fine microstructural details respectively. Hardness of the deformed and annealed samples is measured by Vickers hardness testing. Results show that the grains are refined from 65 µm to 200 nm by ECAP at equivalent strain of 16.8, further grains are refined to <78 nm by cryo-rolling at −50 °C with increase in dislocation density. The cryo-rolling of ultrafine grained (UFG) LCS increases the hardness due to further grain refinement and the increased dislocation density. Hardness of the UFG LCS produced by ECAP is more than three times of coarse grained LCS. Flash annealing (at a range of temperature) of cryo-rolled UFG LCS is produced the single phase bimodal microstructure. Bimodal microstructure is the consequence of secondary recrystallization during flash annealing. Even after flash annealing of ECAP-16.8-CRR-94 deformed sample, hardness is more than 200% of as-received LCS and it decreases with increase in flash annealing temperature. In this study recrystallization, secondary recrystallization and hierarchy in grain growth with increasing annealing temperature is presented. Microstructure and mechanical properties correlation is demonstrated.